Exploring the Impact of Problem-Based Learning and Curiosity on Enhancing Higher-Order Thinking Skills in Elementary Science - Hanifah, Hanifah; Irdalisa, Irdalisa; Kosasih, Ahmad; Akbar, Budhi (Universitas Pendidikan Ganesha, 2025)
High-order thinking skills (HOTS) are important skills that need to be developed early on. The Problem Based Learning (PBL) model as an active learning approach has the potential to improve students' HOTS by involving them in solving real-world problems. This study aims to evaluate the effectiveness of the Problem Based Learning (PBL) model and curiosity in improving high-order thinking skills (HOTS) of fifth-grade elementary school students, as well as to analyze the interaction of the two variables in supporting the development of students' cognitive skills. The research method applied is an experimental study with a 2 x 2 factorial design, involving two independent variables, namely the Problem Based Learning (PBL) model and curiosity, and one dependent variable, namely high-order thinking skills (HOTS). The sample used in this study was 68 fifth-grade students from two elementary schools in Jakarta who were randomly selected using the cluster random sampling technique. The data collection techniques used were through HOTS ability tests, curiosity questionnaires, and observations of the learning process. Data analysis was carried out using a two-way ANOVA test to identify the influence and interaction between variables. In conclusion, the Problem Based Learning (PBL) model is effective to be applied in learning to improve students' HOTS, especially if supported by a high sense of curiosity. This approach can create a more meaningful and relevant learning environment, and become one of the innovative strategies in efforts to improve the quality of learning at the elementary school.